ENHANCING COMMUNITY INCOME THROUGH THE PRODUCTION OF RED GINGER CANDY BASED ON LOCAL POTENTIAL AND DOWNSTREAMING STRATEGIES - Yasmin Chairunisa Muchtar; Muhammad Anggia Muchtar; Jane Melita Keliat; Wina Nurfitriani; Juli Novita Sari; Lailan Syafrina Hasibuan (RADJA PUBLIKA, 2026)
Desa Dalig Raya in Simalungun Regency possesses significant potential in red ginger commodities; however, its utilization remains limited to raw product sales, resulting in low economic value added. This study aims to enhance community income through innovation in processing red ginger into value-added ginger candy based on local potential. The research employs a Participatory Action Research (PAR) approach, involving stages of situation analysis, production training, and business management assistance. The results indicate that the innovation of red ginger candy products improves community skills, increases economic value added, and creates broader market opportunities in functional food products. Furthermore, the program strengthens community economic independence through downstreaming strategies and collaborative partnerships. Overall, this initiative contributes to improving community welfare by optimizing local resources and promoting sustainable rural economic development.